2021
DOI: 10.3390/cancers13133350
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Paclitaxel Efficacy to Suppress Triple-Negative Breast Cancer Progression Using Metronomic Chemotherapy with a Controlled Release System of Electrospun Poly-d-l-Lactide-Co-Glycolide (PLGA) Nanofibers

Abstract: Triple-negative breast cancer (TNBC) is highly aggressive and responds poorly to conventional chemotherapy. The challenge of TNBC therapy is to maximize the efficacies of conventional chemotherapeutic agents and reduce their toxicities. Metronomic chemotherapy using continuous low-dose chemotherapy has been proposed as a new treatment option, but this approach is limited by the selection of drugs. To improve antitumor therapeutic effects, we developed electrospun paclitaxel-loaded poly-d-l-lactide-co-glycolide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…33 PTX with various combinations has been evaluated in patients with TNBC. [33][34][35][36][37][38][39] Co-delivery of PTX and cisplatin using hydrogel showed synergistic effect on MDA-MB-231 cells by inducing apoptosis. 40 A recent clinical trial has reported on the use of PTX with the combination of targeted agents, 41 which disrupt microtubules, 42 induce DNA damage, 43 inhibit cell cycle, 44 induce apoptosis, 45 and reduce angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…33 PTX with various combinations has been evaluated in patients with TNBC. [33][34][35][36][37][38][39] Co-delivery of PTX and cisplatin using hydrogel showed synergistic effect on MDA-MB-231 cells by inducing apoptosis. 40 A recent clinical trial has reported on the use of PTX with the combination of targeted agents, 41 which disrupt microtubules, 42 induce DNA damage, 43 inhibit cell cycle, 44 induce apoptosis, 45 and reduce angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Electrospun membranes should be designed to largely enhance their release quantity over the polymer degradation period and act as carriers to increase their compatibility with an aqueous environment. PLA, PLGA 50:50, and PCL electrospun membranes could achieve logistic release of more than 50% encapsulated PTX or cisplatin for 30 days or longer [ 60 , 63 , 67 , 68 , 71 , 87 , 89 ]. Complex encapsulation techniques like conjugation [ 59 ], dextran encapsulation [ 87 ], blending with chitosan [ 60 ], and release enhancers [ 71 ] were effective in boosting release efficiency (released drug ratio).…”
Section: Release Profiles Of the Chemotherapy Drug-loaded Electrospun...mentioning
confidence: 99%
“…Mechanistically, PTX action includes several signaling pathways in which PTX modulates cellular processes that results in programmed cell death triggering. PTX is considered as the first-line treatment drug in breast cancer (BC), especially in triple negative breast cancer (TNBC) [ 56 ], since this subtype of carcinoma is not sensitive to estrogen receptor positive breast cancer cell. Unfortunately, the resistance of BC to PTX treatment is a great obstacle in clinical applications and one of the major causes of death associated with treatment failure.…”
Section: Lncrna H19 Impairs Chemo and Radiotherapy In Breast Cancermentioning
confidence: 99%